THE EXPLORATION OF ARTIFICIAL INTELLIGENCE AND CREATIVE PEDAGOGY IN TEACHING ENGLISH TO YOUNG LEARNERS (TEYL) - Aly, Abdul Hamid; Rafli, Zainal; Murtadho, Fathiaty (JMIE (Journal of Madrasah Ibtidaiyah Education), 2024)
This ethnographic study investigates the integration of Artificial Intelligence (AI) in creative pedagogy for Teaching English to Young Learners (TEYL) at SD Tahfidz Al Basyir, Bogor. The research explores how AI tools, such as adaptive learning systems and ChatGPT, are employed alongside creative teaching methods to enhance language acquisition and foster creativity among children. Findings reveal that AI significantly contributes to personalized learning, increased student engagement, and the provision of immediate feedback, thereby improving the overall learning experience. However, the study identifies key challenges, including limited access to AI tools, inadequate infrastructure, and insufficient teacher training, which hinder effective AI integration. The research underscores the pivotal role of teachers in mediating AI use and recommends targeted professional development programs to equip educators with the necessary skills. This study not only enhances understanding of AI’s role in creative language pedagogy but also offers practical strategies to optimize AI-based teaching practices, particularly in resource-constrained settings, while addressing equity and accessibility issues.